System of floating solar farm with different anchor cross section - Chua, Wei Yi (Nanyang Technological University, 2023)
Due to limited land availability, Singapore has set a goal of generating 2GW of solar energy by 2030, with floating solar photovoltaic (FPV) farms being a popular option. More research is required to completely comprehend their environmental impact. Sinkers are used to anchor these FPVs, which can create sediment suspensions due to water flow in reservoirs like Tengeh Reservoir. This erosion can disturb the seabed, affecting water quality, and even shifting the FPVs from their intended location. The goal of this research is to find the best anchor shape and configuration to reduce sediment movement caused by the water flow around the anchor and thus safeguard the water quality in Singapore's reservoirs. To reduce the impact of large-scale sediment suspension caused by the sinkers that anchor the FPV, innovative solutions that are cost-effective are needed to mitigate this issue. The research looked into a variety of parameters such as manufacturing techniques, sinker shapes, and the angles of water flow. The study utilizes five distinct sinkers of different properties to compare how the shape and angle cause varying sediment erosion patterns and thus sediments dislodged. The study's overall goal was to determine the most effective anchor shape and configuration for minimizing sediment movement and protecting water purity in Singapore's reservoirs.